CONTEXTUAL ARCHITECTURE: CONSIDERING CLIMATIC AND GEOMORPHOLOGICAL CONDITIONS IN THE DESIGN OF PUBLIC BUILDINGS - Baranovych Л.; Baranovych А.; Savchak Н.; Mykhailechko В. (Bulletin of Lviv National Environmental University. Series «Architecture and Construction», 2025)
When designing any structure or building, it is essential to consider the natural conditions of the site – climate, topography, and geological data. This article explores the significance of natural and climatic factors in the design process of public buildings. The authors emphasize that effective architectural and planning solutions must account for the geographical, climatic, geological, hydrological, and topographical characteristics of the location. Key environmental factors influencing architectural response include solar insolation, temperature, wind, precipitation, and the site's microclimate. Special attention is given to the orientation of buildings relative to cardinal directions, the influence of solar movement throughout the year, natural lighting of interior spaces, and spatial organization considering shadows. The article discusses types of natural and combined lighting as a basis for architectural form-shaping. It examines the role of temperature regimes and wind in the selection of architectural forms, ventilation systems, thermal insulation, and solutions for wind protection. A separate section is devoted to adapting buildings to various climate zones – from cold to hot and humid regions. Architectural strategies that contribute to creating comfortable microclimatic conditions both inside the building and in adjacent areas are analyzed, including the use of planning forms, landscaping, and water elements. Significant focus is placed on topography and terrain: methods for integrating buildings into complex landscapes, the interaction between architectural form and natural surroundings, and planning strategies for sloped sites. The article defines how climatic and natural conditions influence the overall structure, functional zoning, and aesthetic appearance of buildings. Thus, the work substantiates the necessity of a comprehensive analysis of the natural context during the design process, enabling the creation of functional, energy-efficient, and environmentally harmonious architectural objects.